2018
DOI: 10.5812/jjm.68423
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Conventional and Nanosilver-Containing Leucocyte and Platelet-Rich Fibrin/Biomaterial in the Anti-Biofilm Formation of Standard Species of Candida and Streptococcus

Abstract: Background: Biomaterial products like Leukocyte and platelet-rich fibrin (L-PRF) membranes can be used in a variety of medical fields to increase the anti-infective defense system and promote tissue regeneration and wound healing due to platelet growth factors. It is one of the oldest approaches of regenerative tissue. In addition, antifungal and bacterial activities against some microorganisms are reported in the literature for silver nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…Mima et al reported that photodynamic therapy resulted in the reduction of CFU/mL of C. albicans , C. glabrata , C. tropicalis, C. dubliniensis, and C. krusei [ 40 ]. Moreover, inhibition of C. albicans biofilm formation by silver nanoparticles in the surgical sites was reported in the literature [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mima et al reported that photodynamic therapy resulted in the reduction of CFU/mL of C. albicans , C. glabrata , C. tropicalis, C. dubliniensis, and C. krusei [ 40 ]. Moreover, inhibition of C. albicans biofilm formation by silver nanoparticles in the surgical sites was reported in the literature [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRP groups were less inflamed than non-PRP equivalents. PRP and other platelet derivatives are proven to have microbiocidal properties, this may help in not calling inflammatory cells (16,17). Inflammation is likely to degrade the intact collagen and destroy the viable cells, consequently exacerbating the functional deficit and prolonging the recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common oral infections, especially amongst HIV-positive individuals and the elderly population, is oral candidiasis [ 5 , 20 , 24 , 31 , 32 , 33 ]. Also known as “thrush” or “candidosis”, this fungal infection is characterized by Candida spp.…”
Section: Oral Infections: Causative Pathogens and Aggravating Potentialmentioning
confidence: 99%
“…Streptococcus mitis is another type of bacteria in the human mouth that is commonly found in the throat and nasopharynx as a colonized organism. It can cause infection in immunocompromised patients with moderate or severe clinical diseases [ 33 ]. The risk for oral infections by opportunistic bacteria is also increased in individuals taking chemotherapeutic drugs, as this may alter the receptor interaction between pathogens and epithelial cells and increase bacterial adhesion, while reducing the salivary secretion rate and oral pH.…”
Section: Oral Infections: Causative Pathogens and Aggravating Potentialmentioning
confidence: 99%